PENGARUH MEDIA PEMBELAJARAN PICTURE BOOK CAREER TERHADAP PEMAHAMAN PERAN SOSIAL ANAK USIA 5-6 TAHUN DI TK AISYIYAH BUSTANUL ATHFAL PARANG TAMBUNG - Syahrah Riada Syam; A. Sri Wahyuni Asti; Hajerah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the influence of Picture Book Career learning media on the understanding of social roles among children aged 5-6 years at TK Aisyiyah Bustanul Athfal Parang Tambung. This study employed a quantitative approach with a pre-experimental design using a one-group pretest-posttest design. The research subjects consisted of 12 children in group B4 aged 5-6 years. Data collection techniques included observation, performance tests, and documentation. The research data were analyzed using descriptive and inferential statistics with the assistance of IBM SPSS Statistics 25 through the Shapiro-Wilk normality test and the Paired Sample t-Test hypothesis test. The results showed that the use of Picture Book Career learning media had an influence on children’s understanding of social roles at TK Aisyiyah Bustanul Athfal Parang Tambung. This was indicated by the improvement in children’s abilities after being given treatment using Picture Book Career media. Children became more capable of recognizing professions, explaining professional duties, understanding the benefits of professions for the surrounding environment, and demonstrating better social behavior during learning activities and role-playing. Therefore, Picture Book Career media can be used as an effective learning medium to improve young children’s understanding of social roles.